Primary Pulmonary Mucinous Cystadenocarcinoma: A Case Report - Andreas Efstathiou; Christos Asteriou; Nikolaos Barbetakis; Dimosthenis Miliaras; Athanassios Kleontas; Christos Karvelas; Miltiadis Lalountas (Case Reports in Medicine)
Primary pulmonary mucinous cystadenocarcinoma (PMCAC) is an extremely rare cystic neoplasm. A case of a 56-year-old male with a cystic lesion of the right lower lobe is described. Preoperative fine needle aspiration cytology and bronchoscopy were inconclusive. The patient underwent a formal right lower lobectomy and mediastinal lymph node dissection. Diagnosis was established intraoperatively. The biological behavior of primary PMCAC is unknown. Therefore, careful long-term follow-up is considered necessary because of lack of experience globally.